Peningkatan Produktivitas Budidaya Ikan Nila (Oreochromis Niloticus) Melalui Transfer Biofloc Technology (BFT) untuk Mendukung Penguatan Kemandirian Desa Mojorejo, Kecamatan Junrejo, Kota Batu - Soeprijanto, Agoes; Jamroni, Mofit; Aisyah, Diana; Supriyadi, Supriyadi; Subandi, Hendi (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Aquaculture business, especially tilapia cultivation in Mojorejo village, did not run as expected due to low fish production and limited community knowledge regarding cultivation techniques. Some of the problems faced by the cultivator group are that the fishery business has not been well programmed because there is no socialization of business potential in the fishery sector, effective tilapia cultivation techniques are not yet known, and assistance is needed related to aquaculture management to be able to optimize tilapia aquaculture production. So that the main goal in this community service activity is to increase the productivity of tilapia (Oreochromis niloticus) cultivation through transfer of biofloc technology (BFT) to support strengthening the independence of Mojorejo village, Junrejo District, Batu city. The methods used include surveys and site reviews, BFT socialization and training, BFT transfers, and periodic assistance. The results obtained in this activity are that partners understand the basic principles of tilapia aquaculture with the BFT system, partners understand input and output settings in tilapia cultivation with the BFT system, partners can culture biofloc bacteria, partners can know the C:N ratio in aquaculture ponds and partners can cultivate with the BFT system so that added value to production is increasing.